Internet banking and the law in Europe : regulation, financial integration and electronic commerce / Apostolos Ath. Gkoutzinis. - Gkoutzinis, Apostolos Ath (Cambridge University Press, 2006)
The European Union has long sought to create a single financial area across Europe where consumers in one country benefit from financial markets and activities in other countries. With the emergence of the Internet as a platform for the provision of online banking services, the creation of a pan-European market for banking services appeared a realistic proposition. In practice, however, this has not happened. This book asks why and argues that the creation of banking markets via the Internet relies on both available technologies and appropriate laws and regulations. The institutional and legal framework for online banking services in the single European market are examined, as is the level of legal harmonization achieved in the UK, France and Germany under the influence of the EU Directives pertaining to online banking activities.